2012
DOI: 10.1007/s00432-012-1221-3
|View full text |Cite
|
Sign up to set email alerts
|

A prospective multicenter study of treosulfan in elderly patients with recurrent ovarian cancer: results of a planned safety analysis

Abstract: BackgroundTreosulfan, an alkylating agent, has demonstrated activity in recurrent ovarian carcinoma. It is equieffective as oral (p.o.) and intravenous (i.v.) formulation. To explore the preference and compliance of elderly patients regarding p.o. or i.v. treosulfan for the treatment of relapsed ovarian carcinoma, women aged 65 years or older were included in this prospective multicenter study. Since elderly patients usually have several concomitant diseases and experience more treatment toxicity, an interim s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 17 publications
1
10
2
Order By: Relevance
“…As in our study, in total leucopenia and thrombocytopenia were among the most frequently reported grade III/IV toxicities. The frequency of observed thrombocytopenia (7.2%) is comparable with those published by Meier et al (2009) (7.5%) and Mahner et al (2012) (4.0%). In contrast, the frequency of leucopenia observed in the treosulfan i.v.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…As in our study, in total leucopenia and thrombocytopenia were among the most frequently reported grade III/IV toxicities. The frequency of observed thrombocytopenia (7.2%) is comparable with those published by Meier et al (2009) (7.5%) and Mahner et al (2012) (4.0%). In contrast, the frequency of leucopenia observed in the treosulfan i.v.…”
Section: Discussionsupporting
confidence: 90%
“…arm). Toxicities during therapy with intravenous treosulfan had been reported in several previous studies (Meier et al 2009; Mahner et al 2012). However, safety data on therapy with oral treosulfan are rare.…”
Section: Discussionmentioning
confidence: 56%
“…The stimulation of eryptosis contributes to or even accounts for the anemia observed in the vast majority of patients following Treosulfan treatment [10]. Eryptotic erythrocytes are phagocytosed and rapidly cleared from circulating blood [12].…”
Section: Discussionmentioning
confidence: 99%
“…The substance is at least in part effective by triggering apoptosis [2,3,4,5,6,7,8,9]. The most common side effect of Treosulfan treatment is anemia, affecting as many as 88% of the patients [10]. …”
Section: Introductionmentioning
confidence: 99%
“…In elderly women with advanced ovarian cancer (median age 75 years; range 70-82 years), the median number of concomitant diseases was 5 (range 1-9) [29]. The most common comorbidities were hypertension, diabetes mellitus, cardiovascular, and musculoskeletal disease [27,29].…”
Section: Comorbiditiesmentioning
confidence: 99%